Assessing the Effectiveness of Training and Education on the Knowledge about active Management of 3rd Stage Labor by Nurses and Midwives - Memon, Salma; Imdad, Bushra; Aziz, Amina; Aziz, Farhana; Memon, Farzana; Naeem Zafar, Shehla (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To Assess the Effectiveness of Educational Training on Knowledge and practice about Active Management of 3rd Stage of Labor by Nurses and Midwives. METHODOLOGY: A quasi-experimental study was conducted among nurses and midwives in January- June 2020. The participants for the study were selected based on a non-probability convenient sampling technique. In total, 140 nurses and midwives participated in the study (70) in the interventional group and 70 in the control group. Data collection was done via the adopted questionnaire, and the sample size was calculated through an open epi version 3.0 using the Randomized Clinical Trials formula. RESULTS: In this study, in the intervention group, most women were 18-25 years old, whereas only 2.9% of women were over 40 years old in our study. Age group and previous training on the AMTSL variable are significantly associated with the study group variable. There was a significant mean difference in post-knowledge between the control and intervention groups. Furthermore, there was a significant mean difference in post-practice between both groups. The overall post-test Knowledge of nurses revealed that the intervention group had a better understanding than the control group. CONCLUSION: It is concluded from this study that training and education about the active management of the third stage of labor (AMTSL) is as highly effective as post-test Knowledge, and post-training practice scores were higher than pre-test scores. KEYWORDS: AMTSL, Nurse, Knowledge. Labor, Practice, Postpartum Hemorrhage